On Demand Sequential Release of (Sub)Micron Particles Controlled by Size and Temperature. Issue 5 (25th November 2021) - Liu, Yue; Gould, Oliver E. C.; Kratz, Karl; Lendlein, Andreas
Abstract: Polymeric devices capable of releasing submicron particles (subMP) on demand are highly desirable for controlled release systems, sensors, and smart surfaces. Here, a temperature‐memory polymer sheet with a programmable smooth surface served as matrix to embed and release polystyrene subMP controlled by particle size and temperature. subMPs embedding at 80 °C can be released sequentially according to their size (diameter D of 200 nm, 500 nm, 1 µm) when heated. The differences in their embedding extent are determined by the various subMPs sizes and result in their distinct release temperatures. Microparticles of the same size ( D  ≈ 1 µm) incorporated in films at different programming temperatures T p (50, 65, and 80 °C) lead to a sequential release based on the temperature‐memory effect. The change of apparent height over the film surface is quantified using atomic force microscopy and the realization of sequential release is proven by confocal laser scanning microscopy. The demonstration and quantification of on demand subMP release are of technological impact for assembly, particle sorting, and release technologies in microtechnology, catalysis, and controlled release. Abstract : On demand release of selected (sub)micron particles (subMP) from thermo‐sensitive polymer substrate with relevance in microassembly, sorting, and controlled catalysis is presented here. Shape‐memory effect allows release sequence according to subMP size, while temperature‐memory effect releases particles according to embedding temperature.